Statistical Significance Assessment of Streamflow Elasticity of Major Rivers - Liaqat Ali Shah; Afed Ullah Khan; Fayaz Ahmad Khan; Zahoor Khan; Ateeq Ur Rauf; Saif Ur Rahman; Muhammad Junaid Iqbal; Izaz Ahmad; Asim Abbas (Civil Engineering Journal, 2021)
Impacts of climate change on streamflow have long been an issue of concern for water experts. The main aim of this study is to assess the response of streamflow to precipitation and air temperature. In this study elasticity model was used to compute the precipitation and air temperature elasticity of 6 major rivers in Khyber-Pakhtunkhwa (KP) Province, Pakistan. In contrast to temperature elasticity estimator, box plots of precipitation elasticity estimator have low range and standard deviation leading to greater central affinity which produces valid, appropriate, and statistically significant elasticity results. Precipitation is positively correlated with streamflow while the air temperature is both positively and negatively linked with streamflow. 10% variation in precipitation and air temperature produces 12 to 20% and 8 to 18% change in streamflow, respectively. The sensitivity of streamflow to air temperature is higher as compared to precipitation. This research work shows that precipitation elasticity results are statistically valid and realistic as compared to temperature elasticity results. Moreover, it is suggested to support elasticity results by statistical correlation to avoid misleading and unrealistic results. Results of the current study can be used in formulating long term policies regarding streamflow sensitivity in the study region. Doi: 10.28991/cej-2021-03091698 Full Text: PDF